Climate of Extremes : Global Warming Science They Don't Want You to Know. - Michaels, Patrick J. (Cato Institute, 2009)
An in-depth look at consistent, solid science on the other side of the gloom-and-doom global warming story that is rarely reported and pushed aside: that global warming is likely to be modest, and there is no apocalypse on the horizon.